Beyond Tumor Suppression: Senescence in Cancer Stemness and Tumor Dormancy - Francisco Triana-Martínez; María Isabel Loza; Eduardo Domínguez (Cells, 2020)
Here, we provide an overview of the importance of cellular fate in cancer as a group of diseases of abnormal cell growth. Tumor development and progression is a highly dynamic process, with several phases of evolution. The existing evidence about the origin and consequences of cancer cell fate specification (e.g., proliferation, senescence, stemness, dormancy, quiescence, and cell cycle re-entry) in the context of tumor formation and metastasis is discussed. The interplay between these dynamic tumor cell phenotypes, the microenvironment, and the immune system is also reviewed in relation to cancer. We focus on the role of senescence during cancer progression, with a special emphasis on its relationship with stemness and dormancy. Selective interventions on senescence and dormancy cell fates, including the specific targeting of cancer cell populations to prevent detrimental effects in aging and disease, are also reviewed. A new conceptual framework about the impact of synthetic lethal strategies by using senogenics and then senolytics is given, with the promise of future directions on innovative anticancer therapies.